Chemical Composition and Repellent Activity of Achillea vermiculata and Satureja hortensis against Anopheles stephensi - Masoumeh Pirmohammadi; Mansoureh Shayeghi; Hassan Vatandoost; Mohammad Reza Abaei; Ali Mohammadi; Akbar Bagheri; Mehdi Khoobdel; Hasan Bakhshi; Maryam Pirmohammadi; Maryam Tavassoli (Tehran University of Medical Sciences, 2016)
Background: One of the best ways to control the malaria disease and to be protected human against Anopheles mosquito biting is the use of repellents. Throughout repellents, herbal ones may be an appropriate and safe source for protection. Methods: Chemical constituents of Achillea vermiculata and Satoreja hortensis were determined by using gas chromatography-mass spectrometry. Efficacy and the protection time of these plants were assessed on Anopheles stephensi under the laboratory condition. Results: The mean assessed protection time and efficacy for A. vermiculata was 2.16 and 3.16 hours respectively and the obtained ED50 and ED90 for this plant was 5.67 and 63 µl/cm2 respectively. The figured for S. hortensis was 4.16 and 5 hours respectively.  ED50 and ED90 for this plant were 5.63 and 45.75µl/cm2 respectively. Conclusion: Results of investigation showed that S. hortensis plant has an acceptable protection time, therefore, this plant could be considered as a good herbal repellent against anopheles mosquitoes.